VALIDITY OF THE GASTROPODS POPULAR SCIENTIFIC BOOK IN THE PULAU SEMBILAN KOTABARU COASTAL AREA FOR HIGH SCHOOL STUDENTS - Fajeriadi, Hery; Zaini, Muhammad; Dharmono, Dharmono (FMIPA UNNES, 2019)
The cognitive abilities of Indonesian students are still low based on The Learning Curve in 2013, so the quality of education should be improved. One of them with environmental-based learning. Most Indonesians live in coastal areas, and some use snails as alternative dishes. Therefore, snails in coastal areas can be used as a source of learning. Interest in reading Indonesian students is also low, so the need to develop an interesting book and easily understood so that students are interested to read it. So developed a Book of Popular Scientific-based Diversitas Gastropoda in Coastal Areas. This research is the early stage of development research, which is the validation of popular science books. The purpose of this research is to develop a valid popular science book. Validation is done with three experts by giving a validation sheet of popular science books. Validation data were analyzed descriptively categorization. Suggestions and comments from validators become the reference for product revisions. Validation complete when obtaining minimum category valid. The results showed coherence aspect; legibility; active and passive sentences; method; applications and implications; definitions and explanations; and other styles the device obtains very valid category. Aspects of vocabulary; avoid dubious words; and the format obtains a valid category. Based on the results of this study, the popular scientific books developed have met the rules of popular scientific writing that is interesting and easy to understand, so this popular scientific book can be used by the community and students.